Axolotl: A resourceful vertebrate model for regeneration and beyond. Issue 12 (15th August 2022) - Bölük, Aydın; Yavuz, Mervenur; Demircan, Turan
Abstract: The regenerative capacity varies significantly among the animal kingdom. Successful regeneration program in some animals results in the functional restoration of tissues and lost structures. Among the highly regenerative animals, axolotl provides multiple experimental advantages with its many extraordinary characteristics. It has been positioned as a regeneration model organism due to its exceptional renewal capacity, including the internal organs, central nervous system, and appendages, in a scar‐free manner. In addition to this unique regeneration ability, the observed low cancer incidence, its resistance to carcinogens, and the reversing effect of its cell extract on neoplasms strongly suggest its usability in cancer research. Axolotl's longevity and efficient utilization of several anti‐aging mechanisms underline its potential to be employed in aging studies. Key Findings: Vertebrate regeneration models, such as Ambystoma mexicanum (Axolotl), share many functional and structural proteins and signal pathways with mammalians; therefore, conveying the message generated in axolotl to mammals is a realistic expectation. Studies on neotenic animals have revealed the basics of axolotl regeneration's molecular and cellular steps. Several vital molecules with pro‐ or anti‐regenerative properties have been identified using high‐throughput omics technologies. Top‐notch transgenesis and genome engineering methods have been widely employed in axolotls to study gene functions. The low cancer incidence and resistance to carcinogens have made axolotl a promising and intriguing model in cancer research. Besides the extraordinary regenerative capacity and cancer resistance, axolotls also exhibit rejuvenation of tissues upon regeneration even when these tissues are distant from the amputation site.